Analisis Pendidikan Karakter pada Buku Teks Biologi Kurikulum Merdeka di Kelas X Penerbit Erlangga - Febry Latama; Zulfiana Herni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the character education values contained in the Grade X Biology textbook of the Merdeka Curriculum published by Erlangga. This study employed a content analysis method on the Grade X Biology textbook using document analysis techniques based on 18 character education indicators verified by two observers. The findings revealed that the textbook contains most character education values, with religious and discipline values appearing most frequently, while honesty, tolerance, and national spirit values were not identified. Conclusion, the Grade X Biology textbook of the Merdeka Curriculum published by Erlangga has integrated most character education values, although several values still require further reinforcement. Keywords: Biology Textbook, Character Education, Content Analysis